PENINGKATAN KOMPETENSI PROFESIONAL GURU KEWIRAUSAHAAN MELALUI LESSON STUDY BERBASIS PANTAI DAN LAUT - Siti Sri Wulandari (IKIP PGRI Bojonegoro, 2018)
The objective of the research is to improve the professionalism of entrepreneurship teachers in making the implementation plan of learning in accordance with the potential of coastal and marine natural resources in Sidoarjo Indonesia, is expected to be able to create innovative products from coastal and marine resources resources in the coastal and marine based learning plan. The sample was taken by using purposive sampling technique, that is entrepreneurship teacher who attended the lesson study activity based on beach and sea that amounted to 35 of 90 entrepreneurship teachers in Sidoarjo. Data collection using interview technique, documentation, and observation. The data obtained will be analyzed using qualitative with quantitative approach where data are analyzed using percentage formula, analyzed through three activity paths that focus activity, simplify and transfer from rough data to field notes, display data and deliver final result. The conclusion of coastal and marine based study lesson study is very potential in improving the professionalism of entrepreneurship teachers in improving the quality of learning and learning outcomes of learners and can increase student entrepreneurship interest when they finish studying in formal education. Keywords: Teacher Professional Competency, Lesson Study, Coastal EcosystemPembuatan perencanaan pelaksnaan pembelajaran berbasis pantai dan laut bagi guru kewirausahaan di Sidoarjo Indonesia dalam meningkatkan profesionalitasnya sebagai guru merupakan tujuan dari penelitian ini. Harapannya guru kewirausahaan mampu menciptakan produk inovatif dari sumber daya pantai dan laut yang direncanakan dalam pelaksanaan pembelajaran kewirausahaan berbasis pantai dan laut. Jumlah sampel yang diambil sebanyak 35 orang dari 90 orang anggota musyawarah guru mata pelajaran kewirausahaan di Sidoarjo dengan menggunakan teknik purposive sampling. Pengumpulan data mengunakan teknik wawancara, dokumentasi, dan pengamatan. Analisis data menggunakan deskriptif kualitatif dengan pendekatan kuantitatif dimana data dianalisis menggunakan formula presentase, dianalisis melalui tiga alur kegiatan yakni kegiatan memfokuskan, menyederhanakan dan mentransfer dari data kasar ke catatan lapangan, menampilkan data dan menyampaikan hasil akhir. Kesimpulannya bahwa lesson study pada guru kewirausahaan di Sidoarjo yang berbasis pantai dan laut mampu meningkatkan profesionalisme guru kewirausahaan sehingga meningkatkan kualitas pembelajaran, keaktifan siswa dan hasil belajar siswa serta meningkatkan minat berwirausaha siswa. Kata Kunci : Kompetensi Profesional Guru, Lesson Study, Lingkungan Pesisir Pantai Laut